Questioning Turkish Psychological Counselor Trainees' Prejudices towards Some Clients: Reflections of the Social Context - Serdar Körük; Alper Karababa; Ali Ammar Kurt (Indonesian Counselor Association (IKI), 2023)
The purpose of this study is to reveal the prejudices of psychological counselor trainees towards some clients and the sources of these prejudices on a group of Turkish undergraduates of psychological counseling department. The qualitative data obtained from 39 participants were subjected to content analysis. The themes and the categories reached as a result of the analysis were discussed in line with the literature on prejudice in psychological counseling and preview studies been conducted.